2021
DOI: 10.1055/s-0041-1729906
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics in Endoscopic Transsphenoidal Surgery: A Survey of the North American Skull Base Society

Abstract: Objective Different surgical set-ups for endoscopic transsphenoidal surgery (ETS) have been described, but studies on their ergonomics are limited. The aim of this article is to describe present trends in the ergonomics of ETS. Design and Participants A 33-question, web-based survey was sent to North American Skull Base Society members in 2018 and 116 responded to it (16% of all members). Most respondents were from North America (76%), in academic practice (87%), and neurosurgeons (65%); they had mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…2,3 Surgeons performing this type of surgery suffer from discomfort or injuries that are most common in the shoulder, back and neck, especially in the limb holding the endoscope. [2][3][4][5][6][7] In the medium term, this leads to increased fatigue, which can result in risk to the patient, and in the long term, chronic MSK injuries to the surgeon. 8,9 In the case of ESSBS, the surgeon often has to hold the endoscope permanently in the same position for hours without any support.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Surgeons performing this type of surgery suffer from discomfort or injuries that are most common in the shoulder, back and neck, especially in the limb holding the endoscope. [2][3][4][5][6][7] In the medium term, this leads to increased fatigue, which can result in risk to the patient, and in the long term, chronic MSK injuries to the surgeon. 8,9 In the case of ESSBS, the surgeon often has to hold the endoscope permanently in the same position for hours without any support.…”
Section: Introductionmentioning
confidence: 99%
“…1 In a survey of the North American Skull Base Society, 84% of respondents indicated that during these procedures, the patient is positioned in a straight, supine position, with the patient's head placed in a neutral position (46%) or rotated to the side (38%). 2 The operation is predominantly conducted by the primary surgeon standing (94%) using a binostril technique (95%); 80% of respondents believed that ergonomics play an important role in the surgical procedure. 2 Patients with acromegaly and with Cushing disease often undergo this surgical procedure; a common symptom of these conditions is obesity, which can make it difficult for surgeons to position themselves ergonomically while maintaining requisite operative capability.…”
mentioning
confidence: 99%
“…2 The operation is predominantly conducted by the primary surgeon standing (94%) using a binostril technique (95%); 80% of respondents believed that ergonomics play an important role in the surgical procedure. 2 Patients with acromegaly and with Cushing disease often undergo this surgical procedure; a common symptom of these conditions is obesity, which can make it difficult for surgeons to position themselves ergonomically while maintaining requisite operative capability. Conventional positioning involves securing the patient's arm to the torso with taping and tucking of the sheet around it.…”
mentioning
confidence: 99%
See 2 more Smart Citations